Сучасні тенденції у фаховій підготовці майбутніх вихователів до формування мовленнєво-читацької культури дітей старшого дошкільного віку: ізотерапевтичні техніки - Ніколаєску Інна; Nikolaesku Inna; Бондар Вікторія; Bondar Viktoriia; Шинкарьова Валерія; Shynkarova Valeriia (Видавництво «Код», 2025)
Резюме. У науковому доробку авторами представлені нові підходи до фахової підготовки майбутніх вихователів, спрямовані на оволодіння ефективними ізотерапевтичними методиками та їх застосування у практичній діяльності. Обґрунтовано необхідність використання ізотерапії як інноваційного інструменту у формуванні мовленнєвочитацької культури дітей старшого дошкільного віку, що сприяє їхньому гармонійному розвитку та успішній соціалізації. Акцентовано увагу на актуальних питаннях застосування ізотерапевтичних технік у контексті формування мовленнєво-читацької культури дітей старшого дошкільного віку. Наголошено, що використання ізотерапії в освітньому процесі закладів дошкільної освіти передбачає вільне, спонтанне творення художніх робіт дітей з метою виявлення та опрацювання їхніх емоційних і психологічних труднощів.

Abstract. The article addresses the topical issues of applying art therapy techniques in the context of forming the speech and reading culture of older preschool children. It is emphasized that the use of art therapy in the educational process of preschool institutions involves the free, spontaneous creation of children’s artwork to identify and address their emotional and psychological difficulties. The potential of fine arts as an effective means of stimulating speech activity, developing communication skills, and fostering an interest in reading among older preschoolers is explored. The possibilities of using various art therapy techniques, such as drawing, appliqué, sculpting, and collage, for speech development, vocabulary enrichment, and the formation of coherent speech in children during retelling are revealed. The highlighted techniques contribute to the development of attention concentration, motor skills, action planning, creative thinking, and self-control, while allowing children to safely express their emotions. Particular attention is paid to the integration of art therapy techniques into the process of reading and analyzing literary texts, which promotes the development of emotional intelligence, imagination, and creative thinking in children. In their scientific work, the authors present new approaches to the professional training of future educators, aimed at mastering effective art therapy methods and their application in practical activities. The necessity of using art therapy as an innovative tool in the formation of the speech and reading culture of older preschool children, which contributes to their harmonious development and successful socialization, is substantiated. Creative tasks aimed at forming the speech and reading culture of older preschool children through art therapy are proposed. It is noted that creative tasks using art therapy techniques contribute to the development of children’s emotional intelligence. They learn to recognize and express their own emotions, as well as understand the emotional states of other people. This promotes the development of empathy, communication skills, and the ability to establish interpersonal relationships.
Current trends in professional training of future teachers to form speech-reading culture of children of senior preschool age: isotherapeutic techniques
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: фахова підготовка майбутніх вихователів; ізотерапія; мовленнєва та читацька культура; діти старшого дошкільного віку